From the ldeal Language to the Death of a Novel - Kavaliauskas, Tomas (Respectus Philologicus, 2001)
This article analyses what is the "ideal language" in analytical philosophy and literature. G. Frege, L. Wittgenstein, B. Russell are the authors of analytical philosophy whose philosophical ideas are presented here. B. Pasternak, S. Rushdie, T. Sodeika are the authors whose ideas are used in order to present a different understanding of what the "ideal language" is: for analytical philosophy the "ideal language" is such a language, which represents the objective world as supposedly it is, whereas in literature the "ideal language" is not obligated to reflect the reality as it is, since literature itself is a reality.The goal of the article is to find the reason why G. Steiner has announced the death of a novel. The death of a novel is the death of literature as well; thus, the consequences of it are discussed here too. Finally, this essay concludes that language - regardless whether it is literary or analytical - has its own limits.
Keywords: analytical philosophy; literature; a novel; the; objective reality; meaningful sentences; a fact; to express; a human; limited language